2013
DOI: 10.11144/javeriana.upsy12-3.idmp
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational differences in materialist and post-materialist values in a sample of Hispanic New York City residents

Abstract: The present study evaluates the personal values reported by a sample of New York Hispanic residents using an open evaluation format in which the participants identified and prioritized their personal values. Four hundred and forty-five participants were assigned to one of three groups: Young (n= 159), Adult (n= 168) and Senior (n= 118). The values reported were categorized into post-materialist, materialist or non-classifiable. The Percentage Difference Index between post-materialist and materialist values was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Furthermore, this age-related trend shows the same direction of change as the one found for samples of general populations in Spain, German and the United States. [14][15][16][17][18] An exception can be seen by the increase in importance of the money value category for the youngest generation, as students mentioned money as a personal value more than the professionals (a difference of 21.5% with regard to the oldest generation of professionals and 11.8% with regard to the younger generation of professionals). This finding contradicts the results of Daehlen's 46 longitudinal study in which money as a value was more important among professionals than students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this age-related trend shows the same direction of change as the one found for samples of general populations in Spain, German and the United States. [14][15][16][17][18] An exception can be seen by the increase in importance of the money value category for the youngest generation, as students mentioned money as a personal value more than the professionals (a difference of 21.5% with regard to the oldest generation of professionals and 11.8% with regard to the younger generation of professionals). This finding contradicts the results of Daehlen's 46 longitudinal study in which money as a value was more important among professionals than students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored values using an open format have found inconsistencies in the generality and intensity of the change in values predicted by the VCT in a variety of samples including health professionals 13 and Spanish, German and American general populations. [14][15][16][17][18] This study incorporates an open methodology to explore change in values.…”
Section: Introductionmentioning
confidence: 99%
“…These authors conclude that there is a little evidence of major change in value orientation between 1981 and 1999 in Britain, especially young people in this country are moving slightly away from postmaterialism, becoming increasingly rebellious and conscientious (Majima & Savage, 2007). Similar are the conclusions of Roales-Nieto and Segura who conduct a research on value orientation in Spain (Roales-Nieto & Segura, 2010). They also oppose Inglehart's opinion about the change of value orientation in highly developed countries particularly among young people.…”
Section: Theoretical Considerationsmentioning
confidence: 78%
“…Non-material aspects of poverty are associated with the concept of social exclusion, which primarily focuses on the process leading to poverty (Havasi 2002) and emphasizes non-material aspects of poverty such as low education, poor health, isolation, or exclusion from cultural life. Some items (like Roma ethnicity, retirement, old age, or poverty cycle) are considered family values, therefore cannot be classified as unambiguously related to material or non-material aspects of poverty (Roales-Nieto et al 2013). The same applies to items that are more strongly connected to the potential consequences of poverty, such as alcoholism/smoking or crime, and to items that are mostly the driving factors of poverty, like early family founding, large family, low willingness to work, unfavorable mentality, integration problems, and discrimination.…”
Section: The Interpretation Of Poverty and Its Change Over Timementioning
confidence: 99%